2010
DOI: 10.1161/hypertensionaha.110.151522
|View full text |Cite|
|
Sign up to set email alerts
|

Does Dark Chocolate Have a Role in the Prevention and Management of Hypertension?

Abstract: Abstract-The notion that eating chocolate would prevent or treat hypertension is appealing to many who produce and enjoy chocolate. Several studies have documented beneficial effects of dark chocolate on insulin action and endothelial function. However, the published studies on chocolate and blood pressure include a relatively small number of subjects, and results are conflicting. In addition, because of secrecy surrounding the production of chocolate and the unique sociocultural context of this popular food, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…[5][6][7] This was confirmed by a summary of all open-label and double-blind cocoa studies showing that the BP-lowering benefits of cocoa were confined to open label trials only. 23 Contrary to this is a more recent double-blind study, not implemented in the latter summary, showing a significant 4.2-mm Hg decrease in SBP after 30 days of treatment in 16 patients with previous coronary artery disease. 24 In our study we were able to detect a difference of 2.6 mm Hg in ambulatory SBP between groups but found no effect in the NTC group; together with …”
Section: Normal Dose Theobromine Cocoamentioning
confidence: 84%
“…[5][6][7] This was confirmed by a summary of all open-label and double-blind cocoa studies showing that the BP-lowering benefits of cocoa were confined to open label trials only. 23 Contrary to this is a more recent double-blind study, not implemented in the latter summary, showing a significant 4.2-mm Hg decrease in SBP after 30 days of treatment in 16 patients with previous coronary artery disease. 24 In our study we were able to detect a difference of 2.6 mm Hg in ambulatory SBP between groups but found no effect in the NTC group; together with …”
Section: Normal Dose Theobromine Cocoamentioning
confidence: 84%
“…On the other hand, no difference was observed after chocolate intake by symbolic analysis. Although the mechanism still remains under investigation, recent studies have suggested that chronic dark chocolate intake decreases BP 13,15,30,31 and SBP 25,32 , improves endothelial function in healthy subjects [32][33][34][35][36] , and reduces both systolic and DBP in soccer players 37 . The present study only found a reduction in the SBP of healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In a double blind placebo controlled trial of 379 hypertensive subjects given green tea extract 370 mg/d for 3 mo, BP was reduced significantly at 4/4 mmHg with simultaneous decrease in HS CRP, TNF-α, glucose and insulin levels [268] . Dark chocolate (100 g) and cocoa with a high content of polyphenols (30 mg or more) have been shown to significantly reduce BP in humans [272][273][274][275][276][277][278][279][280][281][282][283] . A metaanalysis of 173 hypertensive subjects given cocoa for a mean duration of 2 wk had a significant reduction in BP 4.7/2.8 mmHg (p = 0.002 for SBP and 0.006 for DBP) [276] .…”
Section: Sesamementioning
confidence: 99%